A study of conservation approach on historic government buildings in Kuala Lumpur / Hasnizan Aksah - Aksah, Hasnizan (2009)
Building conservation has become familiar to almost everybody. People often raise issues of conservation in regard historic buildings such as insufficient guidelines to guide the conservation works, lack of maintenance etc. The term of conservation defined as guardianship providing for maintenance, preservation or protection of what presently exists, from being destroyed or changed in an inappropriate manner. This study / research is aimed to investigate the current conservation approach on the historic government buildings which to indentify the conservation approach and guidelines imposed, to identify the issues and problems in conservation projects, and also to recommend for a better approach in preserving and conserving. The methods taken during this research are un-structure interview and questionnaire, site investigation on case studies, data analysis and recommendation is made base on the analysis of data. All issues or problems in conservation process namely preliminary study and planning, dilapidation study, tender document preparation, building conservation works until handover and management of building should be well identified and analyzed. Recommendation for a better approach of conservation approach is important towards the improvement of conservation approach.